Water Filtered Infrared A and Visible Light (wIRA/VIS) Irradiation Reduces Chlamydia trachomatis Infectivity Independent of Targeted Cytokine Inhibition - Kuratli, Jasmin; Pesch, Theresa; Marti, Hanna; Leonard, Cory Ann; Blenn, Christian; Torgerson, Paul; Borel, Nicole (Frontiers in Microbiology, 2018)
Chlamydia trachomatis is the major cause of infectious blindness and represents the most common bacterial sexually transmitted infection worldwide. Considering the potential side effects of antibiotic therapy and increasing threat of antibiotic resistance, alternative therapeutic strategies are needed. Previous studies showed that water filtered infrared A alone (wIRA) or in combination with visible light (wIRA/VIS) reduced C. trachomatis infectivity. Furthermore, wIRA/VIS irradiation led to secretion of pro-inflammatory cytokines similar to that observed upon C. trachomatis infection. We confirmed the results of previous studies, namely that cytokine secretion (IL-6, IL-8, RANTES/CCL5) upon wIRA/VIS treatment, and the subsequent reduction of chlamydial infectivity, are independent of the addition of cycloheximide, a host protein synthesis inhibitor. Reproducible cytokine release upon irradiation indicated that cytokines might be involved in the anti-chlamydial mechanism of wIRA/VIS. This hypothesis was tested by inhibiting IL-6, IL-8 and RANTES secretion in C. trachomatis or mock-infected cells by gene silencing or pharmaceutical inhibition. Celastrol, a substance derived from Trypterygium wilfordii, used in traditional Chinese medicine and known for anti-cancer and anti-inflammatory effects, was used for IL-6 and IL-8 inhibition, while Maraviroc, a competitive CCR5 antagonist and anti-HIV drug, served as a RANTES/CCL5 inhibitor. HeLa cell cytotoxicity and impact on chlamydial morphology, size and inclusion number was evaluated upon increasing inhibitor concentration, and concentrations of 0.1 and 1 µM Celastrol and 10 and 20 µM Maraviroc were subsequently selected for irradiation experiments. Celastrol at any concentration reduced chlamydial infectivity, an effect only observed for 20 µM Maraviroc. Triple dose irradiation (24, 36, 40 hpi) significantly reduced chlamydial infectivity regardless of IL-6, IL-8 or RANTES/CCL5 gene silencing, Celastrol or Maraviroc treatment. Neither gene silencing nor pharmaceutical cytokine inhibition provoked the chlamydial stress response. The anti-chlamydial effect of wIRA/VIS is independent of cytokine inhibition under all conditions evaluated. Thus, factors other than host cell cytokines must be involved in the working mechanism of wIRA/VIS. This study gives a first insight into the working mechanism of wIRA/VIS in relation to an integral component of the host immune system and supports the potential of wIRA/VIS as a promising new tool for treatment in trachoma.